Utilization of Fly Ash in Construction Materials: Review - Triana, Dessy (Jurnal Fondasi, 2023)
Fly ash is the residue from burning coal in thermal power plant, Wich is the most complex anthropogenic material and if the disposal is improper, it will become environmental pollution. The use of fly ash blended cement and sand mixes is growing rapidly in the construction industry. The purpose of utilizing fly ash is to minimize the cost of fly ash disposal, decrease land provision for fly ash disposal, financial benefits, compensation of processing and disposal costs. Fly ash can replace some rare and expensive natural resources. Fly ash has good performance and environmentally friendly. This literature review was conducted systematically. A systematic literature review is defined as the process of identifying, assessing several existing research sources with the purpose of providing specific research answers. Analysis of the main studies on the utilization of fly ash in construction materials focusing on class C fly ash as a substitute for cement, and class F fly ash is a sand substitute. The chemical composition is highly complete with good pozzolanic.  The initial hardening time is reduced between 20 minutes to 260 minutes, final hardening 60 minutes to 260 minutes. Due to high sulfate, class C fly ash takes longer to harden than Class F fly ash. Class C and Class F fly ash with a high aluminosilicate content, and a fine size contributes to the improved workability of concrete. Fly ash can be used as a raw material in various construction industry due it is an oxide-containing material. Fly ash can be utilized for brick producing, ceramic manufacturing, road construction, concrete production and other activities.